Pengukuran Objek 2 Dimensi Dengan Menggunakan Kamera Berbasis LabVIEW - Khairul Amri; Ruzita Sumiati (Jurnal Teknik Mesin, 2018)
Quality Control (QC) is one of the most important components in the manufacturing process. The aim is to determine whether a product is feasible to market. One aspect of QC is the size / dimension of the object to be made. If the size is still within the range of tolerance, then it has passed the QC in terms of size, but if not then it includes a failed product. The problem encountered is that it takes a long time to take measurements, especially objects in the third dimension where each part is different as microdrill, zipper etc. To overcome this weakness, a CCD camera is used as a sensor to record images and then use LabVIEW software to analyze the size of the recorded image. This is a preliminary study so that it is only done for objects with two dimensions with square and circular shapes. From the research that has been done, the measurement with the camera gives results that are almost the same as the use of calipers where the standard deviation fluctuates from 0.3 to 23.8 for circles and 0.54 to 32.05 for squares. Furthermore, the time needed to do one measurement process with the camera ranges from 201 ms to 338 ms whereas using the calipers takes 3 to 5s